Catalytic oxidation of methane to methanol over Cu-CHA with molecular oxygen. Issue 18 (9th August 2021) - Hirayama, Airi; Tsuchimura, Yuka; Yoshida, Hiroshi; Machida, Masato; Nishimura, Shun; Kato, Kazuo; Takahashi, Keisuke; Ohyama, Junya
Abstract : Catalytic production of CH3 OH in a CH4 –O2 –H2 O flow reaction is improved using Cu-CHA having improved redox property involved in the C–H activation of CH4 . Abstract : Direct oxidation of CH4 to CH3 OH using O2 is challenging because of the high stability of CH4 and the relatively high reactivity of CH3 OH. Here, Cu-CHA zeolites are tested for the direct oxidation of CH4 . Catalytic production of CH3 OH in a CH4 –O2 –H2 O flow reaction is improved using CHA type zeolites compared to other zeolites including MOR, BEA, MFI, and FAU zeolites reported previously. In situ X-ray absorption fine structure (XAFS) spectroscopy reveals that the high catalytic activity of Cu-CHA is derived from its redox properties, particularly, the high reducibility of Cu 2+ involved in CH4 activation. The reaction gas concentrations are varied to find the optimized reaction conditions on Cu-CHA. In addition, the reaction mechanism of the direct CH4 oxidation on Cu-CHA is investigated based on not only the effects of gas concentrations but also the isotope gas effects using CD4, 18 O2, and D2 O. It is suggested that the rate-determining step is the C–H activation of CH4, and the selectivity of CH3 OH is determined by the oxidation rate of CH3 OH, which is affected by the O2 and OH group activation rate on Cu-CHA.